2016
DOI: 10.1167/iovs.15-17896
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Target Parameters on Fixation Stability in Normal and Strabismic Monkeys

Abstract: PurposeThe purpose of this study was to assess the effect of fixation target parameters on fixation instability in strabismic monkeys.MethodsOne normal and three exotropic monkeys were presented with four differently shaped fixation targets, with three diameters, during monocular or binocular viewing. Fixation targets were white on a black background or vice versa. Binocular eye movements were recorded using the magnetic search coil technique and fixation stability quantified by calculating the bivariate conto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…In addition, fixation stability may be influenced by several visual factors such as target size, shape, contrast, and luminance. 8 We measured fixation stability in these animals at the different time points and found a temporary improvement in fixation stability of the treated eye when the untreated eye was viewing but no consistent changes when the treated eye was viewing. Dell'Osso et al suggested that tenotomy surgery reduces nystagmus intensity 47,48 in humans with infantile nystagmus syndrome due to manipulation of proprioceptive receptors in the EOM.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, fixation stability may be influenced by several visual factors such as target size, shape, contrast, and luminance. 8 We measured fixation stability in these animals at the different time points and found a temporary improvement in fixation stability of the treated eye when the untreated eye was viewing but no consistent changes when the treated eye was viewing. Dell'Osso et al suggested that tenotomy surgery reduces nystagmus intensity 47,48 in humans with infantile nystagmus syndrome due to manipulation of proprioceptive receptors in the EOM.…”
Section: Discussionmentioning
confidence: 92%
“…Fixation stability of the nonviewing eye was worse at all time points for both the monkeys, consistent with previous studies of fixation stability in strabismic monkeys. 8 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixation instability in strabismus and amblyopia is not only due to fusion maldevelopment nystagmus. Increased drifts and other forms of nystagmus also contribute to fixation instability (Pirdankar & Das 2016, Tusa et al 2001). A recent study in humans has suggested that increased fixation instability in strabismus could result in increased errors in determining the strabismus angle when using clinical testing methods, such as prisms and alternate cover testing (Economides et al 2016).…”
Section: Oculomotor Properties Of Strabismus Replicated In Animal mentioning
confidence: 99%
“…We also showed that fixation instability was influenced by target parameters such as size and shape of the target, in both normal and strabismic monkeys. 23 The goal of the current study was to further investigate the components that contribute to larger fixation instability in strabismus. Specifically, we were interested in investigating the contribution of fixational saccades toward fixation instability in strabismic monkeys, while also investigating the influence of target parameters, such as target shape and size on fixational saccades.…”
mentioning
confidence: 99%